Optimal conditions for the generation system of a SAW gas sensor - URBAŃCZYK, M.; JAKUBIK, W. (Archives of Acoustics, 1996)
The present paper describes the optimal conditions for generating a Surface Acoustic Wave (SAW) for a gas sensor system. For achieving stable operation it is necessary to assure the largest possible distance between the frequency modes. In order to attain this condition, the length between transducers should be decreased accordingly.